Potensi Wisata Edukasi Berbasis Experiential Learning dan Pemasarannya di Kampoeng Kids Kota Batu, Jawa Timur untuk Menjangkau Segmen Pasar Yang Diharapkan - Yuanita Yuanita (Syntax Idea)
Tourism in Indonesia plays a crucial role as an economic sector with the potential for increasing foreign exchange earnings. Batu City, known as a tourist destination, offers various business opportunities related to tourism. Kampoeng Kidz, an educational land in Batu, holds potential as a sustainable tourism destination with its nature-based learning programs and scenic beauty. However, Kampoeng Kidz faces challenges in digital marketing, particularly during the pandemic, which resulted in a decline in visitor numbers. This research aims to develop a digital marketing strategy, with a focus on social media, to enhance visibility and visits to Kampoeng Kidz. In the context of Law No. 10 of 2009 on Tourism, this study highlights the role of tourism in economic development and provides a rationale for the urgency of digital marketing development. The research employs a qualitative descriptive method with the Branding Gelder theory approach. This approach allows for the reduction of irrelevant information, selecting only interesting, important, and useful information (Sugiyono, 2016). The study was conducted at Kampoeng Kidz using data collection techniques such as interviews, documentation, and observation. Data analysis involves data reduction, data presentation, and drawing conclusions. Tourist visit data to attractions in Batu City in 2020 indicate that Kampoeng Kidz had a relatively low number of visitors compared to other tourist attractions. The focus on educational tourism and its pre-pandemic recognition provide the basis for this research. Kampoeng Kidz needs to strengthen its digital marketing, especially through social media, to reach a wider audience.